Reviewing and Criticizing the Islamic Art Book - Abed Taghavi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Argument to Islamic Art is one of the controversial topics in Archaeology and art of Islamic world. Many scholars have written professional articles and books about the origin, function, cognition of art in the Islamic Period. Whatever has caused the definition differences in Islamic art due to different theoretical frameworks and various approaches have been studied so far. These theoretical approaches have been important to coherent presentation of artistic phenomena in the Islamic world. The present book is included as a source book of Islamic art cognition that it has been written based on the Historicism approach. The book has tried to show the important events from the socio-political and cultural evolutions in the Islamic world according to evidence of urban-planning, art, and architecture. The investigation of this book shows that the author has presented general landscape evolutions according to local scale despite the expansion of Islamic governments in political authority. Serious critiques include generalization and descriptive presentation of various events in Islamic world, lack of the determined approach in analyzing the artistic phenomenon, over-focusing on the socio-economic impacts on the production of objects. Finally, this factor has caused that other factors to be ignored.